Globalizing organic : nationalism, neoliberalism, and alternative food in Israel - Grosglik, Rafi (State University of New York Press, 2021)
Globalizing Organic focuses on the globalization of a culture of eating for change and the ways in which local meanings attached to the production of foods embed ecological and social values. Rafi Grosglik examines how organic agriculture was integrated in Israel a state in which agriculture was a key mechanism in promoting Jewish nationalism and in time has become highly mechanized and technologically sophisticated. He explores how organic food, which signifies environmental protection and social equity, has been realized in a country where environmental issues are perceived as less pressing compared to inner political conflicts, the Israeli-Arab conflict, and recurrent wars. Based on more than a decade of ethnographic fieldwork, interviews, and analysis of historical documents and media, Grosglik traces how alternative food movements are affected by global and local trends. He covers a wide range of topics, including the ethos of halutzim (pioneers, Zionist ideological farmers and workers), the utopian visions of the Israeli kibbutz, indigeneity that is claimed both by Palestinians and Jewish settlers in the Gaza Strip and in the West Bank, biblical meanings that have been ascribed to environmental and countercultural ideas, the Americanization of Israeli society, and its neoliberalized economy.